Bacteriocins: Properties and potential use as antimicrobials. Issue 1 (1st December 2021) - Darbandi, Atieh; Asadi, Arezoo; Mahdizade Ari, Marzieh; Ohadi, Elnaz; Talebi, Malihe; Halaj Zadeh, Masoume; Darb Emamie, Amir; Ghanavati, Roya; Kakanj, Maryam
Abstract: A variety of bacteriocins originate from lactic acid bacteria, which have recently been modified by scientists. Many strains of lactic acid bacteria related to food groups could produce bacteriocins or antibacterial proteins highly effective against foodborne pathogens such as Staphylococcus aureus, Pseudomonas fluorescens, P . aeruginosa, Salmonella typhi, Shigella flexneri, Listeria monocytogenes, Escherichia coli O157:H7, and Clostridium botulinum . A wide range of bacteria belonging primarily to the genera Bifidobacterium and Lactobacillus have been characterized with different health‐promoting attributes. Extensive studies and in‐depth understanding of these antimicrobials mechanisms of action could enable scientists to determine their production in specific probiotic lactic acid bacteria, as they are potentially crucial for the final preservation of functional foods or for medicinal applications. In this review study, the structure, classification, mode of operation, safety, and antibacterial properties of bacteriocins as well as their effect on foodborne pathogens and antibiotic‐resistant bacteria were extensively studied. Abstract : Antimicrobial potential of bacteiocins in food preservation.